Portofolio Assessment in EFL Writing Context in Indonesia: A Systematic Literature Review - Septiya Yuza; Pupung Purnawarman; Didi Sukyadi (Linguistic, English Education and Art (LEEA) Journal, 2024)
Portfolio assessment has been the focus of several EFL classroom research studies. However, this study is carried out to explore the development, implementation and both teachers and students’ perceptions of portfolio assessment at university and school level in Indonesian EFL writing context. Five hundred and Fifty-Five (n=555) journal articles were searched through different search engines, only thirty-seven (n=37) recent and relevant publications published between years 2012 to 2022 were met the criteria and included in this study and remaining are excluded. Among inclusions, there were twenty-one (n=21) qualitative research, twelve (n=12) quantitative, two (n=2) mix-mode, and two (n=2) review paper. The overall respondents of the studies were one thousand and fifty (n=1050). The findings of this research reveal that the use of portfolio assessment for assessing student writing had a significant positive effect and was able to improve students' writing skills. In accordance with their perceptions, both teachers and students responded well to portfolio assessment. They agreed that it is essential to use this portfolio for writing in the EFL classroom since it generates substantial results throughout the writing process. Then, the development of the assessment portfolio in Indonesia has continued to progress in parallel with technological advances. The portfolio assessment tool, which is typically a paper-based portfolio, has started to transform into electronic portfolio. By using e-portfolios, both students and teachers may evaluate writing more flexibly via digital platforms that are accessible anytime and anywhere. Keywords: EFL, E-Portfolio Assessment, Indonesia, Portfolio Assessment, Writing.